A mouse-to-man candidate gene study identifies association of chronic otitis media with the loci TGIF1 and FBXO11 - Mahmood F. Bhutta; Jane Lambie; Lindsey Hobson; Anuj Goel; Lena Hafrén; Elisabet Einarsdottir; Petri S. Mattila; Martin Farrall; Steve Brown; Martin J. Burton (Scientific Reports, 2017)
Abstract Chronic otitis media with effusion (COME) is the most common cause of hearing loss in children, and known to have high heritability. Mutant mouse models have identified Fbxo11, Evi1, Tgif1, and Nisch as potential risk loci. We recruited children aged 10 and under undergoing surgical treatment for COME from 35 hospitals in the UK, and their nuclear family. We performed association testing with the loci FBXO11, EVI1, TGIF1 and NISCH and sought to replicate significant results in a case-control cohort from Finland. We tested 1296 families (3828 individuals), and found strength of association with the T allele at rs881835 (p = 0.006, OR 1.39) and the G allele at rs1962914 (p = 0.007, OR 1.58) at TGIF1, and the A allele at rs10490302 (p = 0.016, OR 1.17) and the G allele at rs2537742 (p = 0.038, OR 1.16) at FBXO11. Results were not replicated. This study supports smaller studies that have also suggested association of otitis media with polymorphism at FBX011, but this is the first study to report association with the locus TGIF1. Both FBX011 and TGIF1 are involved in TGF-β signalling, suggesting this pathway may be important in the transition from acute to chronic middle ear inflammation, and a potential molecular target.